Mathematical modelling and optimization of laser beam parameters on microhardness and surface scratch resistance of Al-TiZn alloy. Issue 2 (3rd April 2022) - Jiru, Moera Gutu; Sinha, Devendra Kumar; Beri, Habtamu
ABSTRACT: There is high demand of Aluminium material for various engineering applications but the main problem being low wear and corrosion resistance. Laser beam application for surface modification of engineering materials gets high attention in research and industries due to superior surface performance for wear and corrosion resistance. In the present research article, an attempt has been made to improve the properties of Aluminium by laser surface alloying technology. Laser surface alloying of commercially pure aluminium with titanium and zinc metal powders at 50% combination has been conducted using CO2 laser power from 1600 to 2000 W. The experiments have been planned through design of experiment using Response Surface Methodology (RSM). The mathematical modelling and optimisation of process parameters such as specific laser power scan speed and heat input for optimum value of Micro hardness has been carried out using RSM with three factors and five levels. The statistical significance of the data has been carried out using Analysis of Variance (ANOVA).The alloy made by Al-TiZn shows improved hardness by 47% due to good laser surface alloying which has created dendrite microstructure without any metallurgical defects. The optimised value of laser energy density was found to be 37 J/mm 2 . It has been investigated that the optimum values of laser speed and heat input are 84 m/s and 61.50 watt respectively for micro hardness value of 56HV. Hardness decreases from top alloy zone towards substrate material since high energy creates more depth where the concentration of alloying elements is less. The friction coefficient of Al-TiZn alloy was found to be less by 23% than unalloyed aluminium substrate. The depth of laser alloyed has been increased with laser power and heat input from laser beam. Higher electron microscopy analysis shows that a sound alloying has been created without surface and subsurface defects. The present investigation is expected to help automobile and aerospace industries where the wear and corrosion resistance of the material are of major concern.